Development and Validation of a Reversed-Phase HPLC Method for the Estimation of Zolpidem in Bulk Drug and Tablets - E. Konoz; A. H. Mohsen Sarrafi; R. Abdolahnejad; M. Bahrami-Zonoz (Journal of Chemistry)
In the present study an isocratic reversed-phase high-performance liquid chromatography method was developed for the estimation of zolpidem in bulk drug and pharmaceutical dosage forms. The quantification was carried out on C18 columns. A mixture of acetonitrile-ammonium acetate (pH=8.0, 0.02 M) (60 : 40 v/v) was used as the mobile phase, at flow rate of 1.0 mL/min and the determination wavelength at 245 nm. The retention time of zolpidem was found to be 3–5 min. The validation of the proposed method was carried out for specificity, linearity, accuracy, precision, limit of detection, limit of quantification, and robustness. The linear dynamic range was from 2.5 to 30 μg mL−1. Regression equation was found to be y=0.1416x+0.0183 with correlation coefficient r=0.9996. The percentage recovery obtained for zolpidem was greater than 96.5%. Limit of quantification and limit of detection were found to be 2.5 μg mL−1 and 0.83 μg mL−1, respectively. The developed method can be used for routine quality control analysis of zolpidem in tablet formulations.